2004
DOI: 10.2134/jeq2004.5320
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cadmium Concentrations in Wheat and Barley Grain Using Soil Properties

Abstract: The entry of Cd into the food chain is of concern as it can cause chronic health problems. To investigate the relationship between soil properties and the concentration of Cd in wheat (Triticum aestivum L.) and harley (Hordeum vulgare L.) grain, we analyzed 162 wheat and 215 barley grain samples collected from paired soil and crop surveys in Britain, and wheat and barley samples from two long-term sewage sludge experiments. Cadmium concentrations were much lower in barley grain than in wheat grain under compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(119 citation statements)
references
References 39 publications
7
104
3
1
Order By: Relevance
“…As this survey was done across a wide range of different locations it is expected that the soil properties, which affect the availability and uptake of metals from soils, will be different at different sites. Soil pH has been identified as an important factor in cadmium accumulation in plants (Adams et al, 2004;Zheng et al, 2011;Zhao et al, 2010;Ding et al, 2013Liu et al, 2015. For example, Liu et al (2015) demonstrated that wheat varieties accumulated more cadmium in acidic soils compared to alkaline soils.…”
Section: Discussionmentioning
confidence: 99%
“…As this survey was done across a wide range of different locations it is expected that the soil properties, which affect the availability and uptake of metals from soils, will be different at different sites. Soil pH has been identified as an important factor in cadmium accumulation in plants (Adams et al, 2004;Zheng et al, 2011;Zhao et al, 2010;Ding et al, 2013Liu et al, 2015. For example, Liu et al (2015) demonstrated that wheat varieties accumulated more cadmium in acidic soils compared to alkaline soils.…”
Section: Discussionmentioning
confidence: 99%
“…There have been attempts to correlate the plant uptake with chemically identifiable fractions of trace element in soil (Singh and Kristen, 1998;McBride, 2002McBride, , 2003Adams et al, 2004;Huang et al, 2004;Kuo et al, 2004). The outcomes however were not conclusive as much of the correlations were not generalized.…”
Section: Elementmentioning
confidence: 99%
“…Plant uptake of trace elements is a dynamic process and is influenced by soil and season related factors (McBride, 2002;Adams et al, 2004;Huang et al, 2004;Kuo et al, 2004;Koo et al, 2006). Foods coming from various sources are intermingled in the market places and in food acquisition the consumers typically have no knowledge of their origin.…”
Section: Introductionmentioning
confidence: 99%
“…Contaminants in soil and food has generated discussions, due to the toxic effects in animal and human healths. For example, lung edemas, anemia and hypertension are symptoms associated to metal intoxications (ADAMS et al, 2004). The problems originated by the mineral excessive ingestion are proeminents as function of the high levels of metals in the diet as well as the time interval of utilization of this diet.…”
Section: Introductionmentioning
confidence: 99%